Dermabrasion for Scars and Wire Loop Electrocautery for Rhinophyma - Hom, David B.; Harmon, Jeffrey (Facial Plastic Surgery, 2019)
Dermabrasion and wire loop electrocautery are controlled scalpel-less procedures to remove superficial skin layers to treat dermal surface irregularities. Their postprocedure healing involves healing by secondary intention. The purpose of this paper is to discuss the use of diamond fraise dermabrasion to improve scars and the use of wire loop electrocautery to treat rhinophyma surface irregularities. Both techniques are minimally invasive and low cost, and at the same time, can significantly improve facial skin deformities. An advantage in using wire loop electrocautery for rhinophyma excision is that it is a simple, economic, and very effective technique to sculpt the nose, with minimal intraoperative bleeding. With dermabrasion, pretreatment and postregimens can help improve postprocedure results. Future efforts to modulate the healing from both of these techniques include the potential use of topical growth factors, autologous platelet-rich plasma, or using stem cells to accelerate collagen formation and reepithelization during the postprocedure period.
Keywords: dermabrasion; wire loop electrocautery; scars; rhinophyma